Occupational Licensure and Entrepreneurs: The Case of Tax Preparers in the United States. (October 2019) - Albert, Kyle W.; Galperin, Roman V.; Kacperczyk, Aleksandra
The authors examine the relationship between entrepreneurship and occupational licensure using data on the universe of more than 700, 000 tax preparers in the United States. Prior research suggests that occupational licensure has negative effects on entrepreneurship because it increases the costs of operating a business. By contrast, the authors argue that licensure may allow entrepreneurs to signal quality and enhance their legitimacy. States that require tax preparers to be licensed have higher average rates of entrepreneurship—approximated by tax practice ownership—and, in high-income ZIP codes, more demand for paid preparer services. In the analysis of the introduction of a federal license requirement in tax preparation in 2013, voluntary early adoption of the license by preparers predicts higher chances of survival in the industry. Entrepreneurs are less likely to adopt the license early than are non-entrepreneurs, unless they lack other state-level credentials. Results thus suggest that licensure represents a trade-off for entrepreneurs between the costs of obtaining a license and the benefits of signaling quality and legitimacy.